An Analytical Study of Ocular Manifestations of Diabetes Mellitus in Tertiary Eye Care - Raja , A. M.; Seema , G.; Praveena Daya A. (Advancement and New Understanding in Medical Science Vol. 8, 2024)
Introduction: Diabetes mellitus is the most prevailing medical condition in the world as it causes an array of long-term systemic complications, which have a considerable negative impact on both the patients and the society which typically affects individuals in their most productive years. Ocular complications of diabetes mellitus can be prevented through early diagnosis and treatment. Common ocular complications of diabetes are Retinopathy, cataract, primary open angle glaucoma, neovascular glaucoma and extra ocular muscle palsy. Aim: The objective of this study was to find out the incidence of various ocular complications of diabetes and to determine the relation between the duration of diabetes, age of the diabetics and the occurrence of ocular complications. Materials and Methods: This study included 200 diabetic patients who visited the outpatient department of ophthalmology at Karuna Medical College Hospital, Kerala, India from September 2015 to August 2017. Results: In this study we found that Retinopathy was the most prevalent (60.5%) ocular complication in diabetes followed by cataract (20%), primary open angle glaucoma (4.5%), neovascular glaucoma and extra ocular muscle palsy (3.5%). The most noticeable complication seen with increased duration of diabetes were Non Proliferative Diabetic Retinopathy (NPDR) (42.5%) and Clinically Significant Macular Edema (CSME) (6%). A nonsignificant association was observed between the age of the diabetics and associated ocular complications. Conclusions: Diabetic Retinopathy was the most common ocular complication of diabetes, followed by cataract, primary open angle glaucoma and extra ocular muscle palsy. The prevalence of diabetic ocular complications was higher in patients with longer duration of diabetes. There was no significant association between age of the diabetics and associated ocular complications.